Efficacy of Oral Alprazolam and Mefenamic Acid in Relieving Pain During Pan Retinal Photocoagulation: 10.36351/pjo.v37i1.1084 - Haider, Muhammad Ali; Sattar, Uzma; Ahmad, Iftikhar (Pakistan Journal of Ophthalmology, 2020)
. Purpose: To find out the efficacy of oral Alprazolam and Mefenamic acid in relieving pain during pan retinal photocoagulation in patients with proliferative diabetic retinopathy. Study Design: Quasi experimental study. Place and Duration of Study: Department of Ophthalmology, Al-Ehsan Eye Hospital, Lahore, from January 2018 to December 2018. Methods: Patients were divided into two groups; groups A received one tablet of Xanax (Alprazolam 0.5 mg) and 2 tablets of Ponston Forte (Mefenamic acid 500 mg) an hour before PRP. In group B no pain relieving medicines were prescribed. Proparacaine hydrochloride 0.5% eye drops were instilled in the eye to achieve corneal anesthesia before the procedure in both the groups. Pain was scored, 15 minutes after PRP, using standard verbal rating scale and results were analyzed. Paired sample t-test was used to measure the mean difference in pain between the two groups. A p value of less than 0.01% was considered significant. Results: Five hundred and sixty patients with proliferative diabetic retinopathy (PDR) requiring Pan Retinal Photocoagulation (PRP) were enrolled. There were 272 males and 288 females. Mean age of patients was 64.0 ± 6.8 years. Mean pain score for group A was 4.0 ± 0.6 and for group B was 2.1 ± 0.3. Difference in pain score felt by each group was -1.93 ± 0.7 with significant p value of ? 0.01%. Conclusion: Oral administration of Alprazolam and Mefenamic acid one hour before PRP in patients with proliferative diabetic retinopathy was effective in reducing pain and in attaining patient cooperation during the procedure. Key Words: Pan Retinal Photocoagulation, Pain, Proliferative Diabetic Retinopathy, Alprazolam, Mefenamic acid.